PEMBELAJARAN BAHASA JEPANG MELALUI YOUTUBE (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study discusses about the characteristics of Japanese Language learning paths and the suitability of YouTube video content as a learning medium. The research aims to describe YouTube content that can be used as a learning medium and explain how the Japanese language learning through YouTube fits the Japanese language teaching flow. The data collection technique of this study used the technique of listening, note-taking, and observation techniques (observation). The results of data collection found 10 videos from 4 YouTube channels that have Japanese language learning flow. It can be concluded that of the 10 videos found there is only one video that has the whole Japanese Learning Flow.Key Words: YouTube, Japanese Learning Flow, Japanese Language